Increases in the susceptibility of human endometrial CD4+ T cells to HIV-1 infection post-menopause are not dependent on greater viral receptor expression frequency - vom Steeg, Landon G.; Shen, Zheng; Collins, Jane; Patel, Mickey V.; Barr, Fiona D.; Hopkins, Daniel C.; Ochsenbauer, Christina; Wira, Charles R. (Frontiers in Immunology, 2025)
Epidemiological evidence suggests that post-menopausal women are more susceptible to HIV infection following sexual intercourse than are younger cohorts for reasons that remain unclear. Here, we evaluated how menopause-associated changes in CD4+ T cell numbers and subsets as well as HIV coreceptor expression, particularly CCR5, in the endometrium (EM), endocervix (CX), and ectocervix (ECX) may alter HIV infection susceptibility. Using a tissue-specific mixed cell infection model, we demonstrate that while no changes in CD14+ macrophage infection susceptibility were observed, CD4+ T cell HIV-1 infection frequency increases following menopause in the EM, but not CX nor ECX. Unexpectedly, the CD4+ T cell expression of two known correlates of HIV infection susceptibly, CCR5 and integrin-α4β7, increased following menopause across all three tissues despite only being associated with increased infection frequency in EM derived CD4+ T cells. After controlling for changes in the expression of either receptor, both CCR5 and α4β7 expressing CD4+ T cells isolated from the EM of post-menopausal women remained more susceptible to HIV-1 infection than those isolated from pre-menopausal women. Shifts in T helper subset composition, including increases in Th1 frequency and decreases in Th17 and Treg frequency were also observed in the EM only following menopause, but did not correlate with increased infection frequency. Treatment of EM derived CD4+ T cells with 17β-estradiol (E2) prior to viral infection, reduced infection frequency independent of changes in either CCR5 or α4β7 expression frequency. Our results demonstrate that the susceptibility of EM derived CD4+ T cells to HIV-1 infection increases post menopause but is unlikely to be driven by increased expression frequency of either CCR5 or integrin-α4β7. These findings contribute to our understanding of how advanced age alters HIV infection risk which will become increasingly important as the human population continues to age.